Use of laser capture microdissection to detect integrated HIV-1 DNA in macrophages and astrocytes from autopsy brain tissues - Churchill, Melissa J; Gorry, Paul R; Cowley, Daniel; Lal, Luxshimi; Sonza, Secondo; Purcell, Damian FJ; Thompson, Katherine A; Gabuzda, Dana; McArthur, Justin C; Pardo, Carlos A; Wesselingh, Steven L (Journal of neurovirology, 2006)
The importance of astrocytes as a reservoir of human immunodeficiency virus type 1 (HIV-1) in the brain remains elusive. By combining immunohistochemistry, laser capture microdissection, and triple-nested Alu-PCR, we demonstrate integrated HIV-1 in astrocytes and macrophages isolated directly from autopsy brain tissues of HIV-1-infected subjects. The ability of HIV-1 to integrate in terminally differentiated astrocytes suggests a permanent reservoir of provirus in brain that will impact the development and likely success of strategies aimed at eradicating HIV-1.